Exploration of Orchid Species: First Annual Biodiversity Camp of Neora Valley National Park, Kalimpong, under Gorumara Wildlife Division, West Bengal, India - Yonzone, Rajendra (Plantae Scientia, 2019)
Present paper deals with available Orchid species resources with field availability status and habitat including phenology during field survey and medicinally important species during First Annual Biodiversity Camp of Neora Valley National Park, under Gorumara Wildlife Division, West Bengal, India.